2017
DOI: 10.1080/03007995.2017.1408579
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, neutrophil–platelet score and prognostic nutritional index: do they have prognostic significance in metastatic pancreas cancer?

Abstract: Basal high NLR (>3), advanced age (>60 years), poor ECOG-PS (>2) and cholestasis were independent poor prognostic factors in MPC. However, PNI, NPS and PLR had no prognostic significance (p = .51, p = .86 and p = .062, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In our study, initial NLR was significantly lower in LS patients with mPDAC. Those results are consistent with previous studies as the prognosis role of the NLR has been demonstrated in PDAC in both early and advanced stages . NLR should be considered a stratification factor in further clinical trials in order to determine whether patients with high NLR at diagnosis could benefit from intensified treatment or, on the contrary, should only require palliative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, initial NLR was significantly lower in LS patients with mPDAC. Those results are consistent with previous studies as the prognosis role of the NLR has been demonstrated in PDAC in both early and advanced stages . NLR should be considered a stratification factor in further clinical trials in order to determine whether patients with high NLR at diagnosis could benefit from intensified treatment or, on the contrary, should only require palliative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that previous authors acknowledged the limitations of their meta-analyses and weakness due to intrinsic heterogeneity, including but not limited to small sample size, variability in cut off levels used, variation in demographic patient population, difference in interventions, large spectrum of clinical stage included, endpoint criteria, and retrospective nature of study (10,26). Most importantly there is a recognized publication bias due to inclusion of studies with positive results and possible exclusion of non-published negative results (29,30) Therefore, we urge caution when evaluating both (NLR and PLR) novel biomarkers from our retrospective review of resectable pancreatic adenocarcinoma patients in order to avoid potential controversy.…”
Section: Discussionmentioning
confidence: 99%
“…In the patients with malignant tumours, systemic inflammatory response plays a crucial role in the development and progression of tumours [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. On the other hand, nutritional status has a significant role in the prognosis of these patients [21][22][23].…”
Section: Discussionmentioning
confidence: 99%